Dinamika Konflik Organisasi dalam Akuisisi Perusahaa Teknologi: Analisis Kasus Whatsapp dan Facebook - Nabila, Dhifa; Kusumajanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the dynamics of conflict and collaboration between WhatsApp and Facebook in the context of a corporate acquisition and its implications for organizations and society. The method used is a qualitative approach with literature review and document analysis related to organizational conflict, privacy policies, and the corporate integration process. The results show that the conflict was triggered by differences in organizational values, particularly regarding platform monetization and user privacy protection, which resulted in changes in organizational structure, the departure of WhatsApp's founder, and a decline in public trust. This study concludes that the alignment of strategic vision and organizational values ​​is a critical factor in the success of collaboration after a technology company acquisition. Keywords: Acquisition, Conflict, WhatsApp and Facebook.